(3TQM aQGFO GdCUhd GdeYQha HGdQSGFd ddCfUGQjs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3gPg GdCehQ ZjQ eSdeI CeG GdChd efgG aHeTbhbg GdKdGKI eecf GdfRGY ajg, CeG GdTb GdChd ajbGd ajg Cfg ZjQ XGgQ hCeG GdTbjf GdBNQjf ajbGd ajgeG HYOe KHhJgGs
(3BNQgG (B:s
(3BNQgG(B: (3bhdg(B: (3CeG GdChd adGf Cj CeG YOe LQjGf GdeSJfO GdChd hgh Cf GdLgd dh cGf eGfYG dGSJdRe LhGR GdeNGdaI GdbWYjI ajeG fMf ajg adCfG fbhd GdLgd ajeG fMf ajg eGfY Yfs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs